2000
DOI: 10.1034/j.1399-3011.2000.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

Structures of the intradiskal loops and amino terminus of the G‐protein receptor, rhodopsin

Abstract: The intradiskal surface of the transmembrane protein, rhodopsin, consists of the amino terminal domain and three loops connecting six of the seven transmembrane helices. This surface corresponds to the extracellular surface of other G-protein receptors. Peptides that represent each of the extramembraneous domains on this surface (three loops and the amino terminus) were synthesized. These peptides also included residues which, based on a hydrophobic plot, could be expected to be part of the transmembrane helix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 32 publications
1
44
0
1
Order By: Relevance
“…A large body of literature supports the basic assumption of the model: For example, proteolysis of membrane proteins resulted in fragments containing entire TM sequences (Huang et al 1981), and chemically or recombinantly synthesized TM peptides spontaneously assembled thereby rescuing receptor activity (Kahn and Engelman 1992;Ridge et al 1995;Martin et al 1999;Wrubel et al 1994). Finally, peptides corresponding to the N and C terminus (Harmar 2001;O'Hara et al 1993), loop domains (Bennett et al 2004;Katragadda et al 2001a, b;Yeagle et al 2000) and transmembrane domains (Katragadda et al 2001a, b;Cohen et al 2008;Zheng et al 2006;Musial-Siwek et al 2008;Tian et al 2007;Lau et al 2008;Mobley et al 2007;Neumoin et al 2007) from GPCRs have been found to fold to distinct secondary structures which in certain cases resembled the structures of the corresponding regions of the intact receptor.…”
Section: Introductionmentioning
confidence: 86%
“…A large body of literature supports the basic assumption of the model: For example, proteolysis of membrane proteins resulted in fragments containing entire TM sequences (Huang et al 1981), and chemically or recombinantly synthesized TM peptides spontaneously assembled thereby rescuing receptor activity (Kahn and Engelman 1992;Ridge et al 1995;Martin et al 1999;Wrubel et al 1994). Finally, peptides corresponding to the N and C terminus (Harmar 2001;O'Hara et al 1993), loop domains (Bennett et al 2004;Katragadda et al 2001a, b;Yeagle et al 2000) and transmembrane domains (Katragadda et al 2001a, b;Cohen et al 2008;Zheng et al 2006;Musial-Siwek et al 2008;Tian et al 2007;Lau et al 2008;Mobley et al 2007;Neumoin et al 2007) from GPCRs have been found to fold to distinct secondary structures which in certain cases resembled the structures of the corresponding regions of the intact receptor.…”
Section: Introductionmentioning
confidence: 86%
“…Kennedy and E.A.B., unpublished observations, July 2003) for a chimera containing the N-terminus of CCR5 grafted onto the corresponding region of bacteriorhodopsin, 41 a 7-transmembrane receptor with structural features dissimilar to those of mammalian GPCRs. The recent demonstration of ordered structures for soluble peptides representing each of the extracellular regions of bovine rhodopsin 42 suggests that considerable insight might be gained from structural analysis of peptides derived from the extracellular regions of CCR5 and from comparisons with the structures of peptides from the corresponding regions of CXCR4 and other GPCRs, with and without coreceptor activity. The synthetic peptide approach thus has potential to bring order to the bewildering complexity of HIV-1 Env/coreceptor interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Turning our attention to polypeptide systems, six protein conformations (1PLW [45], 1FUL [46], 1RVS [47], 1EDW [48], 1FDF [49] and 1UBQ [50]) from the Brookhaven National Laboratory Protein Data Bank (PDB) [51] were used as starting configurations for our calculations. Table 1 shows the computed HOMO-LUMO gaps for these structures in vacuo, using the PBE functional.…”
Section: Protein Systemsmentioning
confidence: 99%